The Relationship Between Shooting Practice and Goals in Football Games - Dimas Putra Ramadhan; Rizki Apriliyanto; Topo Yono (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2025)
Shooting skills are one of the basicskill components that every soccer player must have.This research aims to analyze the relationship between shooting practice and the occurrence of goals in football games, with shooting practice as an independent variableand goal occurrenceas the dependent variable.The research design used is correlational.This research was conducted at the Pakusari AkrabClub and the population was all players at the location, which was 50 people. The research sample used a purposive sampling technique with the characteristics of teenage players aged 16-19 years found as many as 15 people. The instrument used was a goal measurement test. Analysis of the methods and results of this test used the help of the Microsoft Excel program and the SPSS 21 for Windows program.The results of the research show a significant relationship between shooting practice and the occurrence of goals in football games at the Akrab Pakusari club with a correlation value of 0.525with thus it can be concluded that shooting practice with the occurrence of goals in soccer games at SSB Akrab is in the